Applicability of nonlinear static procedures for low-rise unreinforced masonry buildings with flexible diaphragms. (15th April 2017) - Nakamura, Yasuto; Derakhshan, Hossein; Griffith, Michael C.; Magenes, Guido; Sheikh, Abdul H.
Highlights: Investigates the applicability of nonlinear static procedures for unreinforced masonry buildings with flexible diaphragms. Identifies the most suitable manner in applying various nonlinear static methods when diaphragms are flexible. Modal pushover analysis is not always suitable for unreinforced masonry buildings with flexible diaphragms. Simple measure is proposed to identify the suitability of single-mode pushover analysis methods. Abstract: The applicability of the N2 method, the modal pushover analysis (MPA) and an adaptive pushover analysis method are investigated for estimating the peak seismic responses of unreinforced masonry buildings with flexible diaphragms. The performance of nonlinear static procedures are compared against the nonlinear time-history analyses of three low-rise building models with various levels of stiffness eccentricity, type of failure mechanisms of piers (rocking or shear), and a range of diaphragm stiffness representing timber floor and roof systems. The results indicate that the MPA is unsuitable for unreinforced masonry buildings with flexible diaphragms, if the building response is shear-dominated. The adaptive method provides the most accurate estimates when the diaphragms are relatively stiff. When the diaphragms are relatively flexible, none of these methods can provide accurate predictions of peak seismic demands. However, conservative results may be obtained with the N2 method, by taking the envelope of pushover analyses carried out using the force distributions proportional to the uniform and linear displacement shapes along the height of the building. The present study has also identified the most suitable parameters/methods for the use of various nonlinear static procedures, such as the location of the control node used in the N2 method and the modal combination rule used in the MPA, for unreinforced masonry buildings with flexible diaphragms.